Qualitative exploration of perceived benefits of care and barriers influencing HIV care in trans Nzoia, Kenya - V. Naanyu; J. Ruff; S. Goodrich; T. Spira; M. Bateganya; C. Toroitich-Ruto; B. Otieno-Nyunya; A. M. Siika; K. Wools-Kaloustian (BMC, 2020)
Abstract Background Substantial efforts have been made to ensure people living with HIV (PLHIV) are linked to and retained in care but many challenges deter care utilization. We report perceived benefits of seeking HIV care and barriers to HIV care that were identified through a formative assessment conducted to advise the development of an alternative care model to deliver antiretroviral treatment therapy (ART) in Trans Nzoia County, Kenya. Methods Data were collected in 2015 through key informant interviews (KIIs), in-depth interviews (IDIs), and focus group discussions (FGDs). The study involved 55 participants of whom 53% were female. Ten KIIs provided community contextual information and viewpoints on the HIV epidemic in Trans Nzoia County while 20 PLHIV (10 male and 10 female) participated in IDIs. Twenty-five individuals living with HIV participated in four FGDs - two groups for men and two for women. Key informants were purposively selected, while every third patient above 18 years at the Kitale HIV Clinic was invited to share their HIV care experience through IDIs or FGDs. Trained research assistants moderated all sessions and audio recordings were transcribed and analyzed thematically. Results Findings showed that PLHIV in Trans Nzoia County used both conventional and complementary alternative care for HIV; however, public health facilities were preferred. Popular perceived benefits of adopting care were relief from symptoms and the chance to live longer. Benefits of care uptake included weight gain, renewed energy, and positive behavior change. Individual-level barriers to HIV care included lack of money and food, use of alternative care, negative side effects of ART, denial, and disclosure difficulties. At the community level, stigma, limited social support for conventional HIV treatment, and poor means of transport were reported. The health system barriers were limited supplies and staff, long distance to conventional HIV care, and unprofessional providers. Conclusions Diverse individual, community and health system barriers continue to affect HIV care-seeking efforts in Kenya. Appreciation of context and lived experiences allows for development of realistic care models.